RELATIONSHIP BETWEEN LUMBAR-PELVIC FUNCTIONAL STABILITY AND LIMB'S FORCE IN YOUNG ATHLETE OF MASCULINE SOCCER AND INDOOR SOCCER (Fiep Bulletin - online, 2013)
It is growing the importance recognition of the static function in the body as stabilization and power generation in all of sports games activities. The stability of the pelvic center is being seen as pivot of an efficient biomechanics that works to maximize the generation of strength and minimize common loads in all sorts of activities. The purpose of this study was to investigate the relationship between muscles stabilization of the center pelvic with the dynamics power of the upper and lower limbs in soccer and indoor soccer young athletes belonging to the Jacarezinho's Municipal Sports School. Participants were 24 male athletes, aged between 13 and 15 years being 12 of indoor soccer and 12 of soccer. The assessment of estimated great load for the extensor chair (EC), flexor table (MF), curved rowing (RF) and supine bench press (SR), and specific tests of maintained trunk's flexion and extension stabilizers and bridges right (D) and left (E) sides. The data were treated with Pearson correlation coefficient with p
Keywords: dynamics force; static stability; pelvic center